Catalog of Coefficients for Estimating Bulk and Shear Moduli as a Function of Lithology - Fanchi, J.R. (Journal of Basic & Applied Sciences, 2021)
The purpose of this paper is to present correlation coefficients for a variety of rock types that can be used in a suitable petroelastic model (PEM). The correlation coefficients for different rock types facilitate the application of a petroelastic model in reservoir flow models. By combining the correlation coefficients and the PEM, it is possible to obtain low-cost estimates of reservoir geophysical attributes. The rock types include dolomite, limestone, high porosity sandstone, poorly consolidated sandstone, tight gas sandstone, and well consolidated Gulf Coast sandstone.